Electricity Consumption and Manufacturing Sector Output in Nigeria: Evidence from ARDL Approach - Chukwuma, Onwe, Joshua; King, Omolara (Energy Economics Letters, 2020)
Energy plays a crucial role to the prosperity of any nation. Energy demands and the continuous existence of the productive sectors of the economy in Nigeria is such that that must be given prompt attention for national progress and productivity to be achieved in these sectors. This paper tries to examine electricity consumption and manufacturing sector output in Nigeria from 1981 to 2019. By employing the Autoregressive Distributed Lagged Model (ARDL) estimation technique. The variables considered for the study include electricity supply, unit of labour and gross capital formation, government expenditure on power, inflation, as independent variables and Manufacturing sector output as dependent variable. Furthermore, the outcome of the ADF unit root test showed a mix order of integration among the variables employed. The study finds a stable long-run relationship amongst the variables ARDL Wald Test. Estimated results shows that electricity consumption has a positive relationship with manufacturing sector output in the short-run and a negative relationship in the long-run. However, there is a significant impact of electricity consumption and manufacturing sector output in Nigeria Based on the findings above, the study recommends that government and policy makers in Nigeria to present a working economic plan for the manufacturing sector which will increase energy generation to the country and mostly to the manufacturing sector as this will increase local contents and promote the activities of small and medium scale enterprise who depend on energy needs in carrying out their operations.